ENGINEERING GEOPHYSICAL RESEARCH FOR MAPPING OF HYDROGEOLOGICAL CONDITIONS OF IMERETI LOWLAND - S. A. Grokholskaya (Известия высших учебных заведений: Геология и разведка, 2016)
The work is devoted to the use and results of the main methods of engineering geophysics in the study of flooding on the territory of Imereti lowland (Sochi, Krasnodar region). The complex research includes the methods of engineering seismic works, electrical DC (direct current) and GPR (ground penetrating radar). Geophysical surveys allowed to specify the geological structure and hydrogeological conditions in the study area, as well as to define the basic physical parameters of soils. It was found that the geological section has a layered structure to a depth of about 100 m, for the each layer the geophysical parameters were found, including the velocity of longitudinal (300÷1950 m/s) and transverse waves (100÷250 m/s), as well as a range of values of the electrical resistance (50÷1000 Ohm · m), relative dielectrical permeability (20-60 units).